Phosphorylation of Arabidopsis NRT1.1 regulates plant stomatal aperture and drought resistance in low nitrate condition - Yuchen Kou; Bodan Su; Shunyao Yang; Wei Gong; Xi Zhang; Xiaoyi Shan (BMC Plant Biology)
Abstract Background NITRATE TRANSPORTER 1.1 (NRT1.1) functions as a dual affinity nitrate transceptor regulated by phosphorylation at threonine residue 101 (T101). Previous studies have suggested that NRT1.1 is involved in stomatal opening and contributes to drought susceptibility. However, the precise mechanism of how the phosphorylation status of NRT1.1 affects stomatal movement and drought tolerance remains unclear. Results In this study, we observed that seedlings expressing the phosphorylated form of NRT1.1 (NRT1.1T101D, T101D) exhibited increased drought tolerance compared to dephosphorylated NRT1.1 (NRT1.1T101A, T101A) mutants under low nitrate (LN) condition, characterized by decreased stomatal aperture and water loss. Moreover, we found that the drought-induced depolarization of membrane potential was diminished in T101D mutants in comparison to T101A seedlings. Furthermore, we revealed that the reduced stomatal opening in T101D seedlings was related with depressed nitrate and potassium influx, along with the down-regulation of NRT1.1, POTASSIUM CHANNEL IN ARABIDOPSIS THALIANA 1, and ARABIDOPSIS $${\text{H}}^{+}$$ H + ATPase 1 in comparison with that of T101A. Conclusions Our study provides several lines of evidence to demonstrate that the phosphorylation of NRT1.1 at T101 contributes to the drought tolerance under LN condition by reducing the influx of nitrate and potassium into the cytoplasm, attenuating membrane depolarization and thereby inducing stomatal closure. This finding identified a novel drought resistance mechanism enabled by post-transcriptional regulation of plasma membrane transporter.